EPISTEMOLOGI TAFSIR AL-SHÂṬIBÎ DALAM MEMAHAMI ALQURAN - Akhmad Roja Badrus Zaman (Diya Al-Afkar: Jurnal Studi al-Quran dan al-Hadis, 2020)
This article reviews the epistemologi of al-Shâṭibî (d. 790H) in interpreting the Alquran and its relevance to the development of interpretations of the Alquran in the contemporary era.  In his capacity as an expert in Islamic law - with his maqasid al-shariah ideas, al-Shâṭibî succeeded in conceptualizing the methodology for the discovery of Islamic law which in turn also came into contact with the interpretation of the Alquran.  This is certainly a natural thing because the Alquran is the main source of Islamic law itself.  From the studies conducted, it can be seen, First, the interpretation method carried out by al-Shâṭibî is classified in the epistemologi of Burhani.  Namely interpretation based on observations which are then systematized with the method of historical criticism (critical history) —especially the linguistic aspects.  While the reasoning arguments used are the demonstrative, verification, and exploratory methods with normative, and philosophical approaches.  Second, the epistemologi of al-Shâṭibî has a significant relevance to the development of scientific scholarship in the contemporary era, particularly in aspects of methodical development and systematization.Keywords: Tafsîr Maqâsidî, Maqâṣid al-sharî’ah, dan Tafsîr al-Shâṭibî Artikel ini mengkaji tentang epistemologi al-Shâṭibî (w. 790H) dalam menafsirkan Alquran serta relevansinya terhadap perkembangan penafsiran Alquran di era kontemporer. Dalam kapasitasnya sebagai seorang pakar hukum Islam—dengan gagasan maqâṣid al-sharî’ah-nya, al-Shâṭibî berhasil mengkonseptualisasikan metodologi penemuan hukum Islam yang pada gilirannya juga bersinggungan dengan penafsiran Alquran. Hal ini tentunya suatu hal yang wajar karena Alquran merupakan sumber utama hukum Islam itu sendiri.  Dari kajian yang dilakukan, dapat diketahui, Pertama, metode penafsiran yang dilakukan al-Shâṭibî tergolong dalam epistemologi burhani. Yaitu penafsiran yang didasarkan pada observasi yang kemudian disistematisasikan dengan metode kritik sejarah (critical history)—khususnya aspek kebahasaan. Sedangkan argumentasi penalaran yang digunakan adalah dengan metode demonstrative, verifikatif, dan eksploratif dengan pendekatan normatif, dan filosofis. Kedua, epistemologi al-Shâṭibî memiliki relevansi yang signifikan terhadap pekembangan keilmuan tafsir di era kontemporer, khususnya dalam aspek pengembangan dan sistematisasi metodis.Kata Kunci: Tafsîr Maqâsidî, Maqâṣid al-sharî’ah, dan Tafsîr al-Shâṭibî